2015
DOI: 10.1007/s00299-015-1837-2
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide accumulation and expression of genes related to parthenolide biosynthesis affected by exogenous application of methyl jasmonate and salicylic acid in Tanacetum parthenium

Abstract: Up-regulation of germacrene A synthase and down-regulation of parthenolide hydroxylase genes play key role in parthenolide accumulation of feverfew plants treated with methyl jasmonate and salicylic acid. Parthenolide is an important sesquiterpene lactone due to its anti-migraine and anti-cancer properties. Parthenolide amount was quantified by high-performance liquid chromatography after foliar application of methyl jasmonate (100 µM) or salicylic acid (1.0 mM) on feverfew leaves in time course experiment (3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…4B) and the expression of all four genes were closely related to rutin biosynthesis. In agreement with these results, MeJA has been identified as a predominant inducer of global genes involved in secondary metabolite pathways in various plants, such as Ocimum basilicum 36 , Tanacetum parthenium 18 and S. khuzistanica Jamzad 35 . All the four genes related to rutin biosynthesis investigated in this study, were upregulated by MeJA and SA treatments.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…4B) and the expression of all four genes were closely related to rutin biosynthesis. In agreement with these results, MeJA has been identified as a predominant inducer of global genes involved in secondary metabolite pathways in various plants, such as Ocimum basilicum 36 , Tanacetum parthenium 18 and S. khuzistanica Jamzad 35 . All the four genes related to rutin biosynthesis investigated in this study, were upregulated by MeJA and SA treatments.…”
Section: Discussionsupporting
confidence: 75%
“…This indicates that probably MeJA has stronger effect on rutin biosynthesis compared with SA. It has been also reported that MeJA was a better elicitor than SA for the production of rosmarinic acid in C. forskohlii hairy root cultures 13 , and also parthenoide production in T. parthenium leaves 18 . As described in a previous report 39 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The polyamines in plants are not only found in cytoplasm, but also in speci ed organelles like mitochondria, chloroplasts, and vacuoles [104][105] to the current results, the content of compatible osmolytes and concentration of antioxidant enzymes were increased and decreased, respectively, with the application of 2.25 mM putrescine. There is evidence that SA causes a rise in the quantity of ROS in the cell, suggesting the existence of a self-induced SA 107 . This is not surprising, as a close correlation was recently reported between the endogenous PA and SA contents 108 , which may be responsible for the negative effects of greater concentrations of putrescine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TP has a long history of use in traditional and folk medicine and it has multiple pharmacologic properties, such as anticancer, anti-inflammatory, cardiotonic, antispasmodic, an emmenagogue [28]. The known chemical constituents in TP are reported to include 3β-hydroxy parthenolide, canin and artecanin, having α-methylene butyrolactone moiety [29]. However, no data have been published on the inhibitory activities of TP toward RLAR, AGEs, sorbitol accumulation, and DPPH radical scavenging regulation.…”
Section: Discussionmentioning
confidence: 99%